The separate and joint effects of the market for corporate control and board effectiveness on R&D valuation. Issue 2 (May 2018) - Chen, Shimin; Srinidhi, Bin; Su, Lixin (Nancy); Tong, Jamie Y
This study finds that stronger market control (measured as fewer anti-takeover provisions) and more effective boards (measured as boards that are more independent and for which independent directors have more outside directorships) are both associated with higher R&D valuation. Furthermore, stronger market control (more effective board governance) is associated with higher R&D valuation only in the presence of weaker board governance (market control). Taken together, the results are consistent with the interpretation that both the market for corporate control and effective boards mitigate agency conflicts arising from R&D investments and improve the market valuation of R&D. Furthermore, the two mechanisms act as substitutes in doing so. JEL Classification:G34, G32, M41